1971
DOI: 10.1063/1.1693258
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Shape of Isolated and Pairs of Water Drops in an Electric Field

Abstract: A numerical method of calculating the correct stable equilibrium shape of a conducting drop subject to electrical forces is described. Its application to the problem of the stability of an isolated water drop of undistorted radius R and surface tension T situated in an electric field E indicates that a drop is unstable if E(R/T)12 exceeds a value of 1.603 and its maximum stable deformation expressed as a/b, the ratio of the major to minor axes is 1.83. The numerical method is also applied to a study of the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

1972
1972
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 5 publications
3
39
1
Order By: Relevance
“…Grimm and Beauchamp [30] also investigated the formation of these sprays. They found that neutral droplets exhibited the same prolate elongation mentioned by Brazier-Smith [29] with symmetric "cone jets" of positive and negative progeny droplets. Droplets with a net charge q take the form of asymmetric tear shapes and emit a single charged jet.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Grimm and Beauchamp [30] also investigated the formation of these sprays. They found that neutral droplets exhibited the same prolate elongation mentioned by Brazier-Smith [29] with symmetric "cone jets" of positive and negative progeny droplets. Droplets with a net charge q take the form of asymmetric tear shapes and emit a single charged jet.…”
Section: Introductionmentioning
confidence: 57%
“…Consequently, the instabilities mentioned by Refs. [29][30][31] can be seen even when the droplet charge is way below its Rayleigh limit.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations